Accelerating clinical trial development in vaccinology: COVID-19 and beyond. (June 2022) - Corey, Lawrence; Miner, Maurine D
Abstract : The remarkable success of the US government-backed COVID-19 vaccine development in 2020 offers several lessons on how to effectively foster rapid vaccine discovery and development. Conceptually, the formation of a public–private partnership that included innovative government and academic involvement at all levels of the program was instrumental in promulgating and overseeing the effort. Decades of NIH-sponsored research on vaccine backbones, immunogen design, and clinical trial operations enabled evaluation of vaccine candidates within months of pathogen discovery. Operation Warp Speed fostered industry participation, permitted accelerated movement from preclinical/early phase to efficacy trials, and developed structured clinical trial testing that allowed independent assessment of, yet reasonable comparison between, each vaccine platform by harmonizing protocols, endpoints, laboratories, and statistical analytical criteria for efficacy. This coordinated effort by the US government, pharmaceutical companies, regulators, and academic research institutions resulted in the streamlined, safe, and transparent development and deployment of multiple COVID-19 vaccines in under a year. Lessons learned from this collaborative endeavor should be used to advance additional vaccines of public health importance. Highlights: Public–private partnerships improve the vaccine development process. Long-standing government-sponsored research allowed rapid COVID-19 vaccine rollout. Transparency by all parties involved ensured a robust clinical program.